Influence of the Certified Public Accountant Licensure Examination on Accounting Students’ Attitudes - Aniceto, Maybel Joy A.; Ollier, Kristian Cesar C.; Palicdon, Cherry Rose P.; Gamozo, Kristine Joy A. (Future Science / FSH-PH Publications, 2024)
This research explores the influence of the Certified Public Accountant Licensure Examination (CPALE) on the attitudes and readiness of accountancy students, aiming to improve program outcomes and board examination results. The study surveyed predominantly female respondents aged 19-29, with a monthly family income below 9,520 and a general weighted average ranging from 2.34 to 1.66. Key findings indicate that CPALE significantly affects students' interest and commitment to the program, particularly in enhancing time management skills and study dedication. While demographic factors such as age, gender, family income, and academic performance showed minor program perceptions and preparedness variations, no statistically significant impact was observed. Moreover, a positive correlation was identified between program choice, preparation, and academic practices like group study and practice testing. These findings will help to develop evidence-based techniques and interventions to help students prepare for CPALE, improve their study habits, and increase their overall success rates. Recommendations include involving first and second-year students in future studies, organizing initiatives to boost male enrollment, and promoting comprehensive training and mock exams. Workshops focusing on study habits, time management, and personality development are proposed to enhance student readiness. These findings emphasize the importance of inclusive educational strategies to support all students, regardless of socioeconomic background, and suggest a need for tailored approaches in program design to optimize student preparation and success in the accountancy field.